The Enrichment Mechanism of REE at Sulfate and Methane Transition Zone (SMTZ) of the Northern Part of the South China Sea. (24th February 2022) - Rui, Xie; Daidai, Wu; Jiangong, Wei; Liaoliang, Wang; Lihua, Liu; Wenjing, Li; Gang, Wu; Xudong, Guo
Abstract : Rare earth elements (REE) are important raw materials for electronic products and green-energy technology and deep-sea sediment as an important potential source of REE mineral. It is of great scientific significance to understand the influence of REE in deep-sea sediments. In this paper, thirty sediments samples and eleven sediments samples were collected at the site SH3 and SH1 of Shenhu area, respectively. The trace elements, major elements, and different Fe-Mn minerals were analyzed to investigate the role of anaerobic oxidation of methane (AOM) in the enrichment of rare earth elements in the marine sediments. The result showed that the content of ∑REE/Ti increased at the top of sulfate and methane transition zone (SMTZ) at site SH1 and SH3. Combined with the analysis of different forms of ferromanganese minerals and the REE patterns, it is inferred that there is little influence of terrigenous input to the REE content. In contrary, the REE-rich carbonate phase and REE-rich Fe-Mn oxides (hydroxides) phase have important contribution of REE enrichment at the top of SMTZ. Meanwhile, the calculations of the quantitative relationship between the REE-rich carbonate phase and REE-rich Fe-Mn oxides (hydroxides) phase also confirm this conclusion. And the AOM caused the decrease of the REE-rich Fe-Mn oxides (hydroxides) phase and increase of the REE-rich carbonate phase. This is the potential explanation of ∑REE/Ti enrichment at the top of SMTZ. This study is of great scientific significance for the study of REE enrichment mechanism in the methane seeps and provided a new sight of REE enrichment mechanism in deep-sea sediments.